2010
DOI: 10.1016/j.appet.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the consumption of foods low in saturated fats among people diagnosed with Type 2 diabetes and cardiovascular disease. The role of planning in the theory of planned behaviour

Abstract: 2 AbstractThe present study tested the utility of an extended version of the theory of planned behaviour that included a measure of planning, in the prediction of eating foods low in saturated fats among adults diagnosed with Type 2 diabetes and/or cardiovascular disease. Participants (N = 184) completed questionnaires assessing standard theory of planned behaviour measures (attitude, subjective norm and perceived behavioural control) and the additional volitional variable of planning in relation to eating foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…For example, knowledge of ingredients and label reading, confidence to ask questions about contamination, and being prepared and organised were all associated with better intention and adherence, consistent with a recent study that assessed the consumption of low-fat foods in people with type II diabetes, and found that the extent of planning surrounding eating low-fat foods mediated the relationship between intention and behaviour (White, Terry, Troup, Rempel, & Norman, 2010).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…For example, knowledge of ingredients and label reading, confidence to ask questions about contamination, and being prepared and organised were all associated with better intention and adherence, consistent with a recent study that assessed the consumption of low-fat foods in people with type II diabetes, and found that the extent of planning surrounding eating low-fat foods mediated the relationship between intention and behaviour (White, Terry, Troup, Rempel, & Norman, 2010).…”
supporting
confidence: 84%
“…It may be the case that planning represents the factor that allows for the translation of intention into behaviour White et al, 2010). In the present case the fact that increased planning was mentioned as part of the PBC construct may indicate that although a positive attitude contributes to the development of intention, when it comes to the behaviour it is the increased perception of control (including planning) that determines how strictly the diet is followed.…”
Section: The Tpb and Gfd Adherencementioning
confidence: 68%
“…items measuring the four constructs of the TPB was created by modifying items (to reflect therapy attendance behaviours and processes) used in previous questionnaires in the health field [e.g., 37,21,38]. We initially considered using grounded theory (a qualitative procedure that attempts to uncover views that participants have about a topic [39]), to develop the questionnaire, but this method is used to develop items in the absence of pre-existing theory and research.…”
Section: Therapy Attitudes and Process Questionnaire (Tap) An Originmentioning
confidence: 99%
“…The TPB has been shown to successfully predict intention and behaviour in a number of dietary behaviours (Berg, Jonsson, & Conner, 2000;Collins & Mullan, 2011;Conner, Norman, & Bell, 2002;Fila & Smith, 2006;Kothe, Mullan, & Butow, In Press;Sainsbury & Mullan, 2011;Seo, Lee, & Nam, 2011;Verbeke & Vackier, 2005;White, Terry, Troup, Rempel, & Norman, 2010). The TPB has also been shown to be relatively strong in predicting breakfast skipping in young adult populations (Kothe, Amaratunga, & Mullan, 2011;Wong & Mullan, 2009).…”
mentioning
confidence: 99%